A New Inhibition Kinetic Spectrophotometric Method for the Determination of Resorcinol - Mohsen Keyvanfard (E-Journal of Chemistry)
A new, simple, inexpensive and fast kinetic spectrophotometric method was developed for the determination of trace amounts of resorcinol over the range of 0.02-0.80 μg/mL. The method is based on the inhibitory effect of resorcinol on the formaldehyde catalyzed oxidation reaction of of cresyl violet by bromate in acidic media is reported. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of cresyl violet at 596 nm with a fixed-time 0.5–2.5 min from initiation of the reaction.The detection limit is 0.017 μg/mL and relative standard deviation of 0.1 and 0.5 μg/mL resorcinol for six replicate measurements was 2.6 and 2.9 %, respectively. The method was applied to the determination of resorcinol in water samples.